Meningkatkan Kemampuan Pengucapan Kata melalui Metode Direct Instruction bagi Anak Tunadaksa - Ana Yulia; Kasiyati (Ranah Research : Journal of Multidisciplinary Research and Development, 2020)
In this study the researcher made observations on one subject of a child with disabilities in which he experienced speech delays. To develop the children's speaking ability, the researchers did pronunciation exercises in which there were bilabial letters using the direct instruction method. The type of research used is single subject research (SSR) with A-B-A design. The results of this study found that the direct instruction method can improve the ability to pronounce words for children with disabilities. Based on the results of the research, the pronunciation of words using the direct instruction method can improve the pronunciation of words in which there are bilabial letters in children with disabilities. This can be seen in the baseline conditions (A1) the ability to pronounce words in which there are bilabial letters is still low as evidenced by the results obtained by the children, namely 10%, In the intervention condition (B) after the intervention using the direct instruction method, the ability to pronounce words in which there are increased bilabial letters is proven by the child getting scores, namely 80% . Whereas in the baseline condition (A2) after the intervention was stopped or not given anymore because the ability to pronounce the word which contained the child's bilabial letters had increased by getting a score of 80%. Overlap data in the analysis between conditions, at baseline (A1) and intervention (B) conditions was 100% and the results of the comparison analysis between the intervention conditions (B) and the baseline conditions (A2) showed that the percentage of overlap data was 37,5%. The smaller the overlap percentage, the better the effect of the intervention on changing target behavior in this research.